Implementasi nilai-nilai pancasila pada kehidupan santri di pondok pesantren annajah denanyar jombang - Sya'baniyah, Najwa (Maliki Interdisciplinary Journal, 2025)
Pancasila is not just the foundation of the state, but also the soul and direction of life of the Indonesian nation. The noble values ​​contained therein have proven to be able to unite diversity and provide guidelines in living the life of the nation and state. In the context of Islamic boarding schools, the values ​​of Pancasila have high relevance as moral and social provisions for students. This study highlights how the implementation of Pancasila values ​​is applied in daily life at the Annajah Islamic Boarding School, Jombang. Through a salafiyah education approach that is synergized with formal education, this Islamic boarding school instills the values ​​of Divinity, Humanity, Unity, Democracy, and Social Justice in various religious, social, and institutional activities. The results of the study show that the values ​​of Pancasila do not only live in the theoretical space, but are also manifested in the practical lives of students. Islamic boarding schools as Islamic educational institutions play an important role in shaping the character of students who are religious and nationalistic, who are ready to contribute positively in society.